Queering rurality: reading The Miseducation of Cameron Post geographically. Issue 3 (4th May 2017) - Pini, Barbara; Keys, Wendy; Marshall, Elizabeth
ABSTRACT: This paper contributes to research on geographies of queer rural youth through an analysis of an award-winning young adult novel, The Miseducation of Cameron Post by Danforth (2012a. The Miseducation of Cameron Post . New York: Harper Collins). Three themes from the text are explored in this paper. The first is the well documented heterosexism of rural life. We note that the main protagonist, Cameron Post, experiences rural life on the margins, not only because of her queer identity but also because of her age and gender. A second theme in Danforth's text is that rural spaces can be transgressively queer. In this respect the author subverts conflations of rurality and heterosexuality and urbanity and homosexuality as well as universalising notions of rurality as static, repressive and exclusive. The final theme emerging from a geographical reading of the text is that of placelessness. While highlighting the pervasiveness of this theme, we note that it elicits criticism from readers in relation to the book's ending as it departs from the norms of familiar coming-out-narratives. In conclusion, we emphasise the efficacy of young adult literature as a source for furthering geographic knowledge about young people and sexuality.